2023
DOI: 10.1136/jnis-2023-020220
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for large vessel recanalization before stroke thrombectomy: the HALT score

Abstract: BackgroundLarge vessel recanalization (LVR) before endovascular therapy (EVT) for acute large vessel ischemic strokes is a poorly understood phenomenon. Better understanding of predictors for LVR is important for optimizing stroke triage and patient selection for bridging thrombolysis.MethodsIn this retrospective cohort study, consecutive patients presenting to a comprehensive stroke center for EVT treatment were identified from 2018 to 2022. Demographic information, clinical characteristics, intravenous throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The DTA approach was higher in M1 MCA occlusions (43.2% vs. 27.4%, p=0.038) and basilar occlusions (7.6% vs. 0, p=0.026). DTA patients had a higher NIHSS at the spoke (median NIHSS 15 [9][10][11][12][13][14][15][16][17][18][19][20][21] vs. 9 [4.75-14], p<0.001) and the hub (14 [7][8][9][10][11][12][13][14][15][16][17][18][19][20] vs. 7 [3-15.75], p<0.001). There was no significant difference between the DTA and CTP groups in regards to mRS at 90 days (39% vs. 48.4%, p=0.101).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DTA approach was higher in M1 MCA occlusions (43.2% vs. 27.4%, p=0.038) and basilar occlusions (7.6% vs. 0, p=0.026). DTA patients had a higher NIHSS at the spoke (median NIHSS 15 [9][10][11][12][13][14][15][16][17][18][19][20][21] vs. 9 [4.75-14], p<0.001) and the hub (14 [7][8][9][10][11][12][13][14][15][16][17][18][19][20] vs. 7 [3-15.75], p<0.001). There was no significant difference between the DTA and CTP groups in regards to mRS at 90 days (39% vs. 48.4%, p=0.101).…”
Section: Resultsmentioning
confidence: 99%
“…Gao et al suggested that the clinical and economic benefits of pre-MT may be increased in the drip-and-ship model 20 . Recently, Colasurdo et al suggested the HALT score as a predictor for LVO recanalization prior to thrombectomy; with one of the predictors being early thrombolysis 21 . By identifying some of these factors before arrival to the hub, we may be able to avoid unnecessary angiography activation in certain situations and transferring first to advanced imaging may be reasonable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation